Enhanced progressive fusion method for the efficient detection of multi-scale lightweight citrus fruits - Zeng, Yanlin; Lin, Yao; He, Yiting; Li, Tong; Li, Jing; Wang, Baijuan; Yang, Yi (International Journal of Agricultural and Biological Engineering, 2024)
Human labor efficiency has become unable to keep the pace with gradually annual citrus increasing production. Highly efficient and intelligent citrus picking and accurate yield estimation is the key to solve the problem. Success heavily depends on detection accuracy, prediction speed, and easy model deployment. Traditional target detection methods often fail to achieve balanced results in all those aspects. An improved YOLOv8 network model with four significant features is proposed. First, a lightweight FasterNet network structure was introduced to the backbone network, which reduced the number of parameters and computations while maintaining high-precision detection. Second, a progressive feature pyramid network AFPN structure was added to the neck network. Third, a parallel multi-branch attention mechanism PMBA was added before the detection head to improve the sensing ability after the feature fusion network. Fourth, a Wise-IoU was introduced to replace the original CIoU loss function to make the whole training process converge faster. Based on this, this study proposes an improved version of the YOLOv8 model: the FAP-YOLOv8. This improved model achieved an average accuracy (mAP@0.5) of 97.2% on the citrus datasets, with an accuracy that was 4.7% higher than the original YOLOv8, which was 19.2%, 7.4%, 5.1%, 4.9%, and 5.2% higher than the other models: Faster R-CNN, CenterNet, YOLOv5s, YOLOx-s, and YOLOv7, respectively. The number of parameters was reduced by 55.45%, the computation was reduced by 20% compared to the YOLOv8 benchmark, and the frame rate reached 46.51 fps to meet the detection requirements of lightweight networks. The experiments showed that the FAP-YOLOv8 models all outperformed the comparison models. Consequently, the proposed FAP-YOLOv8 model can help solve the citrus detection problem in orchards, which can be better applied to edge devices and provides strong support for intelligent orchard management. Keywords: citrus fruit detection, enhanced progressive fusion model, multi-scale lightweight, attention mechanism DOI: 10.25165/j.ijabe.20241706.8802 Citation: Zeng Y L, Lin Y, He Y T, Li T, Li J, Wang B J, et al. Enhanced progressive fusion method for the efficient detection of multi-scale lightweight citrus fruits. Int J Agric & Biol Eng, 2024; 17(6): 218–229.